Correlation of EDLC Capacitance with Physical Properties of Polyethylene Terephthalate Added Pitch-Based Activated Carbon - Cheol Hwan Kwak; Dohwan Kim; Byong Chol Bai (Molecules, 2022)
The electric double-layer capacitor (EDLC) has attracted attention by using activated carbon (AC) as an active electrode material with a high power density and high cost-efficiency in industrial applications. The EDLC has been actively developed over the past decade to improve the power density and capacitance. Extensive studies on EDLCs have been conducted to investigate the relation of EDLC capacitance to the physical properties of AC, such as the specific surface area, pore type and size, and electrical conductivity. In this study, EDLC was fabricated with AC, and its capacitance was evaluated with the physical properties of AC. The AC was prepared using petroleum-based pitch synthesized using pyrolysis fuel oil (PFO) with polyethylene terephthalate (PET). The AC based on PFO and PET (PPAC) exhibited high specific surface area and low micropore fraction compared to the PFO-based AC without PET addition (PAC). Furthermore, the reduction of the EDLC capacitance of PPAC was smaller than that of PAC, as the scan rate was increased from 5 to 100 mV s−1. It was determined that the minor reduction of capacitance with an increase in the scan rate resulted from the development of 4 nm-sized mesopores in PPAC. In addition, a comprehensive correlation of EDLC capacitance with various physical properties of ACs, such as specific surface area, pore characteristics, and electrical conductivity, was established. Finally, the optimal properties of AC were thereupon derived to improve the EDLC capacitance.